2021
DOI: 10.2514/1.b38037
|View full text |Cite
|
Sign up to set email alerts
|

Thrust Validation of Rotating Detonation Engine System by Moving Rocket Sled Test

Abstract: This Paper presents the results of a rotating detonation engine rocket sled test demonstration on a 127 mm gauge rail at 100 m long high-speed running track test equipment to evaluate the thrust performance of a stand-alone rotating detonation engine propulsion system. The developed sled test demonstrator contained all onboard subsystems, including engine, gas cylinders, valves, controller, and a data logger. The sled test demonstrator successfully generated thrust, and three or four detonation waves of 1460 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As the reported thermal efficiency for the near constant volume combustion (in pressure gain combustor) is 20% more than the constant pressure combustion in a thermodynamic cycle such as Brayton cycle, detonation wave engines have become the natural choice for the futuristic systems. A moving rocket sled test has been performed by Goto et al 5 for a RDE integrated with a spike nozzle which generated a specific impulse of 144 s with 3-4 detonations waves of velocity 1460-1800 m/s. RDE is being evaluated for Rocketdyne's RL-10 rocket and upper stages of Delta IV and Atlas V rockets.…”
Section: Introductionmentioning
confidence: 99%
“…As the reported thermal efficiency for the near constant volume combustion (in pressure gain combustor) is 20% more than the constant pressure combustion in a thermodynamic cycle such as Brayton cycle, detonation wave engines have become the natural choice for the futuristic systems. A moving rocket sled test has been performed by Goto et al 5 for a RDE integrated with a spike nozzle which generated a specific impulse of 144 s with 3-4 detonations waves of velocity 1460-1800 m/s. RDE is being evaluated for Rocketdyne's RL-10 rocket and upper stages of Delta IV and Atlas V rockets.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 13 ] found that in the flow field of the anti-D-shaped rocket sled, the unsteady large-scale vortex and shock motions appeared due to the strong momentum transfer, and the axisymmetric geometry was suitable for the rocket sled. A rocket sled test with a rotating detonation engine (RDE) was conducted by Goto et al [ 14 ]. The combustor pressure and the specific impulse of the sled test were comparable to the results of the laboratory stand firing test using a load cell.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Journell et al [12] analyzed the combustion process of the RDE operating at working conditions similar to gas turbines by means of chemiluminescence and particle image velocimetry (PIV). Goto et al [13] conducted a rocket sled test for the thrust performance assessment of an RDE with an inner diameter of 60.5 mm. Thrust was generated for 2 seconds and a specific impulse of 144 s was measured.…”
Section: Introductionmentioning
confidence: 99%